Wave resource variability: Impacts on wave power supply over regional to international scales - Ian Masters (Energy Procedia, 2017)
The intermittent, irregular and variable nature of the wave energy resource has implications for the supply of wave-generated electricity into the grid; intermittency of renewable power may lead to frequency and voltage fluctuations in the transmission and distribution networks. This study analyses the wave resource over different spatial scales to investigate the potential impacts of the resource variability on the grid supply. It is found that the deployment of multiple wave energy sites results in a reduction in step changes in power, leading to an overall smoothing of the wave-generated electrical power.